Analisis Faktor-Faktor yang Mempengaruhi Kelemahan Pengendalian Internal Pemerintah Daerah (Studi Kasus pada Kabupaten dan Kota di Provinsi Jawa Tengah Periode 2011-2012) - Nurwati, Ika; , Dra. Rina Trisnawati, M.Si, Ph.D, Akt, CA (2015)
The study entitle "an analysis of the factors that affectingInternal Control Weakness of local government (case study in the District and the city of Central Java province in the period 2011-2012)". The purpose of this study was to examine the Size,Economy Growth, population,PAD, and capital expenditures of the local goverment to internal control weaknesses. The population in this study is the city and regency of Central Java province. They are 35 regencies and cities as sample of this research. The sampling technique used saturated sampletechniques. The secondary data used in this study . It sourced from www.bpk.go.id, www.bps.go.id and www.djpk.go.id. The hypothesis tested by multiple linear regression analysis. The results of the researchindicate that size, economic growth, and the PAD have no effect on internalcontrol weaknesses. While thepopulation and capital expenditures have significantly affect on internal control weaknesses. Keywords: Internal Control Weaknesses, Size, Economic Growth, Population, PAD, and Capital Expenditures.